A core–shell structured magnetic Ag/AgBr@Fe2O3 composite with enhanced photocatalytic activity for organic pollutant degradation and antibacterium. Issue 87 (20th September 2015) - Huang, Shuquan; Xu, Yuanguo; Chen, Zhigang; Xie, Meng; Xu, Hui; He, Minqiang; Li, Huaming; Zhang, Qi
<x xml:space="preserve">Abstract</x> A core–shell structured Ag/AgBr@Fe2O3 composite was prepared successfully. It has magnetic properties, highly efficient photocatalytic activity and antibacterial ability.